Protocol for the quantitative detection of mtDNA in the supernatants of activated human naive CD8+ T cells - Linlin Li; Jun Jin (STAR Protocols)
Summary: Here, we present a protocol for the quantitative characterization of human T cell aging. We describe steps for sample collection; peripheral blood mononuclear cell (PBMC) isolation; and the enrichment, assessment, and activation of naive CD8+ T cells. We then detail procedures for supernatant collection and quantification using the absolute copy number of mitochondrial DNA (mtDNA) released into the supernatants from in-vitro-activated naive CD8+ T cells. We also apply this approach to predict the occurrence of lung adenocarcinoma in middle-aged populations.For complete details on the use and execution of this protocol, please refer to Jin et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.